An initial characterization of aflatoxin B1 contamination of maize sold in the principal retail markets of Kigali, Rwanda - Nishimwe, Kizito; Wanjuki, I.; Karangwa, C.; Darnell, Ross; Harvey, Jagger J.W. (Elsevier, 2017)
Food security considerations have shifted in recent years, with the recognition that available food should also be nutritious and safe. There is a growing evidence base for contamination of maize and other crops by fungal toxins in the tropics and sub-tropics. As an initial snapshot of contamination by one of these toxins in Rwanda, Aflatoxin B1 (AFB1) was analyzed in 684 samples of maize flour collected in seven principal retail markets of Kigali and in 21 samples of animal feed from seven feed vendors. Two rounds of sample collections were carried out, the first in September 2014 and the second in January 2015. A questionnaire given to vendors was used to determine if gender and education level of vendors, origin of maize and awareness of aflatoxins had any significant effect on AFB1 level in collected samples. Enzyme-Linked Immunosorbent Assay (ELISA) and Immuno-affinity fluorimetery were used to analyze samples. Only markets had a significant effect on AFB1 level; for the two collections, differences were inconsistent among markets. In the first round, market means of AFB1 varied between 8.0 ± 5.57 μg/kg and 24.7 ± 23.74 μg/kg and for the second round, between 10.4 ± 8.4 μg/kg and 25.7 ± 25.85 μg/kg. In most animal feed samples AFB1 was >100 μg/kg. None of the vendors interviewed was aware of the risk of mycotoxin contamination in their maize-based flours and feed. Limits set by the United States Food and Drug Administration (20 μg/kg) for total aflatoxins and European Commission (2 μg/kg) for AFB1 for maize flour imports, were varied between 2–35% and 66–100% of samples, respectively. The implications of this study for human and animal health in Rwanda suggest that expanded surveys are needed to understand the scope of contamination, given the influence of environment and other factors on aflatoxin accumulation. Available options to mitigate and monitor aflatoxin contamination can be further deployed to reduce contamination.